2016
DOI: 10.1371/journal.pone.0167495
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium, Magnesium, Zinc and Copper Levels in Sudanese Women with Preeclampsia

Abstract: BackgroundAlthough the exact pathophysiology of preeclampsia is not fully understood, several elemental micronutrient abnormalities have been suggested to play a contributory role in preeclampsia.AimsTo investigate the levels of calcium, magnesium, zinc and copper in women with preeclampsia.Subjects and MethodsA case—control study was conducted in Omdurman Maternity Hospital, Sudan, during the period of September through December 2014. The cases were women with preeclampsia while healthy pregnant women were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 39 publications
2
42
0
1
Order By: Relevance
“…Researchers have identified several risk factors that may be associated with PE/E, including health and lifestyle risk factors, such as smoking, alcohol consumption, obesity, family history, nulliparity, and chronic hypertension (Duckitt andHarrington 2005, UN General Assembly 2011). Several micronutrient, mineral, and trace element deficiencies are also reportedly linked with PE/E risk; a recent systematic review identified associations between iron deficiency, low magnesium, and selenium during pregnancy with PE/E (Elmugabil et al 2016, Kirk and Dempsey 2016, Xu et al 2016). An association between hypertension and PE/E specifically, with high salinity (salt) drinking water, has been reported, prompting this research study.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified several risk factors that may be associated with PE/E, including health and lifestyle risk factors, such as smoking, alcohol consumption, obesity, family history, nulliparity, and chronic hypertension (Duckitt andHarrington 2005, UN General Assembly 2011). Several micronutrient, mineral, and trace element deficiencies are also reportedly linked with PE/E risk; a recent systematic review identified associations between iron deficiency, low magnesium, and selenium during pregnancy with PE/E (Elmugabil et al 2016, Kirk and Dempsey 2016, Xu et al 2016). An association between hypertension and PE/E specifically, with high salinity (salt) drinking water, has been reported, prompting this research study.…”
Section: Introductionmentioning
confidence: 99%
“…Negative correlation was also observed between serum calcium and MAP in first trimester of pregnancy (r = −0.288, p = 0.007). There are research evidences that documented an inverse relationship between intake of calcium in pregnancy and incidence of preeclampsia [42] [43]. In 2011, WHO recommended calcium supplementation with 1.5 -2.0 g per day in calcium deficient pregnant women for the prevention of pregnancy hypertensive disorders [44].…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] Meanwhile, some studies nd no associations. [20] Furthermore, to our knowledge, little information is available in the association between copper level during early or mid-term pregnancy and preeclampsia and separately by its subtype. Therefore, research on copper level during early or mid-term pregnancy and preeclampsia is of paramount importance for clinician.…”
Section: Introductionmentioning
confidence: 99%